Implementasi Kebijakan Pemberlakuan Pembatasan Kegiatan Masyarakat Kota Semarang - Rosiana Purwita N; Endang Larasati; Retno Sunu Astuti; Teuku Afrizal (PERSPEKTIF, 2022)
The Indonesian government makes a policy to carry out community service through the Large-Scale Social Restriction (PSBB) policy. The government issued this policy to suppress the spread of Covid-19 in Indonesia. The implementation of this policy is also carried out in the city of Semarang, so there is a need for a scientific study to measure the implementation of the PPKM policy in the city of Semarang. This research is a type of qualitative descriptive research. This study uses data sources from scientific journals, book literature, and official websites, which are then described through descriptive analysis. The assessment of this implementation uses four variables from George III: communication, resources, disposition and organizational structure. The results of this study indicate that the communication carried out by the Semarang City Government is to conduct outreach directly to the community regarding PPKM policies. The organizational structure, in this case, the Semarang City Government, formed a task force consisting of various elements in the city of Semarang as a supporter of the implementation of the policy. This study concludes that there are still many layers of society in the city of Semarang who think that the policy hinders community mobility in carrying out work, so there is still a lack of public understanding. Therefore, the Semarang City Government needs to work together with community leaders to provide an understanding of PPKM policies.